The contribution of microfinance to the development of small enterprises in Algeria. (The experience of the National Agency for the Management of Microcredit 2005-2019). - zouake, haoues (Journal of Research in Finance and Accounting, 2021)
This study attempted to shed light on the role of microfinance in the development of small enterprises in Algeria, given their economic and social importance, based on the experience of the National Agency for Microcredit Management. It reached a set of conclusions and made a set of proposals that could contribute to the establishment of an integrated microfinance system in Algeria.